The Relation of Group Performance to the Age of Members in Homogeneous Groups - Webber, Ross A. (Academy of Management Journal, 1974)
The article discusses the findings of a study on the relation of a homogeneous group's performance to the age of its members. The study asked four hundred individuals and 80 five-person groups from management development programs and university classes to complete two 25-item vocabulary synonym exercises. Group score was found to be positively associated with the prior performance of group members on the individual exercise. Research also suggests that younger groups are less competitive and hence more cooperative in group settings.